2016
DOI: 10.1002/2015gb005333
|View full text |Cite
|
Sign up to set email alerts
|

Linking temperature sensitivity of soil CO2 release to substrate, environmental, and microbial properties across alpine ecosystems

Abstract: Our knowledge of fundamental drivers of the temperature sensitivity (Q10) of soil carbon dioxide (CO2) release is crucial for improving the predictability of soil carbon dynamics in Earth System Models. However, patterns and determinants of Q10 over a broad geographic scale are not fully understood, especially in alpine ecosystems. Here we addressed this issue by incubating surface soils (0–10 cm) obtained from 156 sites across Tibetan alpine grasslands. Q10 was estimated from the dynamics of the soil CO2 rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 66 publications
4
98
0
1
Order By: Relevance
“…Ding et al . () found that Q 10 was negatively correlated with sand content after 10 days of pre‐incubation for soils at 156 grassland sites across the Tibetan Plateau. However, Wei et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ding et al . () found that Q 10 was negatively correlated with sand content after 10 days of pre‐incubation for soils at 156 grassland sites across the Tibetan Plateau. However, Wei et al .…”
Section: Discussionmentioning
confidence: 97%
“…If C in finer soil particles has a larger Q 10 , C cycling in finer‐textured soils might be more sensitive to climate warming, and vice versa . Although several studies have explored the relation between Q 10 and soil texture (Hamdi et al ., ; Ding et al ., ), the outcome is elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude and direction of the positive feedback between the global C cycle and climate warming strongly depend on the temperature sensitivity ( Q 10 ) of Rs (Davidson & Janssens, ; Heimann & Reichstein, ). Variations in Rs across different climatic conditions and soil types were comprehensively investigated (Colman & Schimel, ; Ding et al., ; Fierer, Colman, Schimel, & Jackson, ; Liu et al., ; Peng, Piao, Wang, Sun, & Shen, ). However, these variations remain controversial because of the large spatial heterogeneity in the decomposability of soil organic matter (Schmidt, Torn, Abiven, Dittmar, & Guggenberger, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the Q 10 of Rs has gained increasing concerns, and is strongly affected by the incubation temperature (Craine, Spurr, McLauchlan, & Fierer, ; Hamdi, Moyano, Sall, Bernoux, & Chevallier, ), C quality (Sihi, Inglett, & Inglett, ; Xu, Luo, & Zhou, ), and soil microbial characteristics (Ding et al., ; Karhu et al., ; Thiessen, Gleixner, Wutzler, & Reichstein, ). However, the relative importance of these factors in the regulation of Q 10 is difficult to quantify because they often interact with each other (Colman & Schimel, ; Fierer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Using a large-scale incubation experiment, Colman & Schimel (2013) found that soil microbial biomass was the most important factor explaining the spatial variation of soil microbial respiration in North America, while climate and substrate only exerted slight indirect effects through their impacts on microbial biomass. Recently, a study conducted under varying temperatures of 5-25°C demonstrated that precipitation was the best predictor of soil microbial respiration rates in the alpine steppes of China (Ding et al, 2016). In previous decades, the C quality temperature (CQT) hypothesis was proposed to explain the relationship between SOM decomposition and soil substrate quality across different ecosystems.…”
Section: Introductionmentioning
confidence: 99%